Coral communities condition in varying wave exposure: the gulf of Cazones, Cuba - Caballero Aragon, Hansel (2016)
Wave exposure can influence community structure and distribution of shallow coral reefs, by affecting organisms both directly and indirectly. To assess the current stony coral community condition under different degrees of wave exposure at a marine protected area of the Gulf of Cazones (SW Cuba), two expeditions were carried out in May 2010 and June 2012. Four sampling sites were sampled at reef crests (1.5 m deep), and twelve at fore-reefs, at 10, 15 and 20 m deep in four geographic locations. Live coral cover, species richness and composition, colony density, and maximum diameter were assessed using the AGRRA 2001 methodology. Multivariate and non-parametric statistics were applied to compare sites. The coral community structure within reef crests was not homogenous. The observed variability of indicators apparently was determined by great coral mortality events resulting from natural disturbances that occurred in the past (hurricanes, bleaching and diseases). Fore-reef coral communities displayed better condition and lower coral mortality than reef crests. Species richness and coral composition varied, while multivariate and statistical methods did not reveal site grouping with regard to wave exposure. The remaining biological condition indicators were similar among sites, except in the most exposed one, where coral cover and coral size were slightly lower. Wave exposure in the gulf of Cazones seemed not to have a significant influence on differences in condition and structure of the assessed coral communities.